2012
DOI: 10.1103/physrevc.85.064917
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a spectral modification of theρmeson on the shear viscosity of a pion gas

Abstract: We evaluate the shear viscosity of a pion gas in the relativistic kinetic theory approach. The in-medium propagator of the ρ meson at finite temperature is used to evaluate the π − π scattering amplitude in the medium. The real and imaginary parts of the self-energy calculated from one-loop diagrams are seen to have noticeable effects on the scattering cross-section. The consequences on temperature dependence of the shear viscosity evaluated in the Chapman-Enskog and relaxation time approximations are studied.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
68
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 32 publications
(75 citation statements)
references
References 45 publications
7
68
0
Order By: Relevance
“…[32], it was shown that a KT approach leads to an η of the pionic medium that increases with T when a phenomenological interaction is used, while a decreasing function of T is obtained when using χ PT in that same approach. An increasing trend of η with T was also observed by Mitra et al [40,41], who incorporated a medium dependent π -π cross section in the transport equation for a pion gas. They also found a significant effect of a temperature-dependent pionic chemical potential [41].…”
Section: Introductionsupporting
confidence: 49%
See 2 more Smart Citations
“…[32], it was shown that a KT approach leads to an η of the pionic medium that increases with T when a phenomenological interaction is used, while a decreasing function of T is obtained when using χ PT in that same approach. An increasing trend of η with T was also observed by Mitra et al [40,41], who incorporated a medium dependent π -π cross section in the transport equation for a pion gas. They also found a significant effect of a temperature-dependent pionic chemical potential [41].…”
Section: Introductionsupporting
confidence: 49%
“…[36,40,44,45] predicted a shear viscosity η of pionic matter that increases with T , whereas using a Kubo approach, Lang et al [39] predicted η to decrease with T . For the interaction of pions in the medium, Lang et al [39] used lowest order chiral perturbation theory (χ PT), which describes well the experimental data on π -π cross sections up to center-of-mass energies of √ s = 0.500 GeV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…I |M I | 2 and ignoring the non-resonant I = 2 contribution, the cross-section is found to agree very well [28,29] with the estimate based on measured phase-shifts given in [6]. In this way it is ensured that the dynamical model is normalized against experimental data although, this approach of introducing the width is not quite in agreement with low energy theorems based on chiral symmetry.…”
Section: Sukanya Mitra and Sourav Sarkarmentioning
confidence: 57%
“…In almost all estimations of the transport coefficients a vacuum cross-section was employed. In [28,29] a medium dependent cross-section was used in the evaluation of shear and bulk viscosities of a pion gas which resulted in a significant deviation from the results obtained with the ππ cross-section in vacuum.In this work we study the temperature dependence of the thermal conductivity of a pion gas. In particular, our intention is to emphasize on the effect of the medium on its temperature dependence brought in by the crosssection.…”
mentioning
confidence: 99%